2013
DOI: 10.1007/s00244-013-9965-6
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons and Metals in Transplanted Lichen (Pseudovernia furfuracea) at Sites Adjacent to a Solid-waste Landfill in Central Italy

Abstract: The aim of the study was to evaluate the airborne contamination by polycyclic aromatic hydrocarbons (PAHs) and some heavy metals (arsenic [As], cadmium [Cd], chromium [Cr], copper [Cu], nickel [Ni], lead [Pb], and zinc [Zn]) of different pollution scenarios around a solid-waste landfill in central Italy using the lichen Pseudovernia furfuracea as a monitoring tool. For this purpose, eight stations around a landfill characterized by different air pollution sources (industrial, agricultural, residential areas, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
22
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
6
22
1
Order By: Relevance
“…The collections of lichen thalli were performed following the same previously reported methodology (Guidotti et al 2009;Protano et al 2014). The collected lichen sample was divided into 13 homogeneous subsamples of approximately 10 g. One subsample served as field blank (unexposed control sample) and was immediately analysed for all study analytes, while the remaining 12 subsamples were each placed in a bag (20 9 20 cm) of 1-cm mesh nylon netting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The collections of lichen thalli were performed following the same previously reported methodology (Guidotti et al 2009;Protano et al 2014). The collected lichen sample was divided into 13 homogeneous subsamples of approximately 10 g. One subsample served as field blank (unexposed control sample) and was immediately analysed for all study analytes, while the remaining 12 subsamples were each placed in a bag (20 9 20 cm) of 1-cm mesh nylon netting.…”
Section: Methodsmentioning
confidence: 99%
“…This sampling period was chosen to have similar climatic conditions to those of our previous biomonitoring studies conducted with the same lichen species under various scenarios of air pollution (Guidotti et al 2009;Protano et al 2014). In addition, the sampling period was also selected to assess the level of air pollution when the incinerator operated at full load, and to avoid any reduction in the ability of lichen to serve as a biomonitor and bioaccumulator, which is known to occur during the typical summer climatic conditions in western countries (Bergamaschi et al 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…or R. farinacea accumulated more low molecular weight POPs (3-and 4-ringed PAHs) than foliose lichen P. sulcata which was enriched in high molecular weight POPs (5 and 6-ringed PAHs). Lichen biomonitoring studies indicated that PAHs with 2-4 rings are dominated in lichen thallus (Augusto et al 2010;Blasco et al 2011;Bajpai et al 2013;Shukla et al 2013;Nascimbene et al 2014;Protano et al 2014) while in the case of PCDD/Fs, the lichen accumulated mostly from TCDD/Fs to PeCDD/Fs (Augusto et al 2007). Lichens accumulated higher PAH concentrations when compared with other environmental indicators (Fig.…”
Section: Persistent Organic Pollutants (Pops)mentioning
confidence: 97%
“…PAHs pollution present in the ecosystem can be efficiently detected by lichen biomonitoring techniques, and a large number of PAH accumulation in lichens from different regions of the world are available (Guidotti et al 2003;Blasco et al 2006Blasco et al , 2011Augusto et al 2009a;Shukla et al 2010Shukla et al , 2013Nascimbene et al 2014;Protano et al 2014). …”
Section: Persistent Organic Pollutants (Pops)mentioning
confidence: 98%